Influence of Surfactants on the Activity Powders of Barium Hexaferrite, Prepared by Wet Grinding - V.G. Andreev; V.G. Kostishyn; A.G. Nalogin; A.Yu. Adamtsov; P.A. Ryapolov (Журнал нано- та електронної фізики)
Study the influence of citric acid and isopropyl alcohol on processes of wet grinding mixture of starting ferrite constituting components and synthesized ferrite charge. Found that the introduction of additives during wet grinding allows to significantly reduce the temperature of synthesis and sintering ferrite raw blanks. Increased activity of powders is explained by the formation of active the gelled layers on the surface of particles in the process of wet grinding.